Comparing Titration Practices in Educational Institutions with Varied Accreditation Levels - Orden, Carina B. (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: The study aims to compare the titration practices and the student-to-burette ratio among institutions with varied accreditation levels in Albay, Philippines. Methodology: The descriptive survey compared titration practices and student-to-burette ratio across educational institutions stratified with varied accreditation levels. The population was Chemistry Instructors and Laboratory Custodians from 15 institutions, totalling 30 respondents, with a sample size of 24 respondents. Data was collected using Survey Instruments for Chemistry Instructors and Laboratory Custodians. Statistical analysis included descriptive and inferential statistical analysis with a chi-square test of association and Cramer’s V effect size (α = 0.05). Main Findings: Associations between accreditation level, conduct, and availability of reagents for neutralization and complexometric titrations, chi-square test of association, and Cramer’s V effect size (α 0.05) were found. The student-to-burette ratio ranged from 1 to 4 students (Level IV and III) and 40+ students (II and I) per acid and base burettes to no burettes in Level I institutions. The reasons for the non-performance of the titration activities were: lack of materials, training, and experience, assistance in the laboratory, and class size. Novelty/Originality of this study: This study examines how accreditation levels and titration resources are associated with titration education. The challenges and strengths of titration education in Albay, Philippines, might not be captured in national and international studies. The holistic approach of evaluating titration practices, resource availability, and student-to-burette ratio provides a comprehensive picture of titration education in the province.